Sectoral Heterogeneity, Resource Depletion, and Directed Technical Change: Theory and Policy - Karen Pittel; Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
We analyze an economy in which sectors are heterogeneous with respect to the intensity of natural resource use. Long-term dynamics are driven by resource prices, sectoral composition, and directed technical change. We study the balanced growth path and determine stability conditions. Technical change is found to be biased towards the resource-intensive sector. Resource taxes have no impact on dynamics except when the tax rate varies over time. Constant research subsidies raise the growth rate while increasing subsidies have the opposite effect. We also find that supporting sectors by providing them with productivity enhancing public goods can raise the growth rate of the economy and additionally provide an effective tool for structural policy.
Keywords: O4; O41; Q01; Q3; 330; sustainable development; sectoral heterogeneity; directed technical change; Wirtschaftswachstum; Mehrsektoren-Modell; Nachhaltige Entwicklung; Erschöpfbare Ressourcen; Technischer Fortschritt; Wachstumstheorie; Theorie